Infectious diseases, parasites, and diet of game fish from lakes, rivers, and streams on Fort McCoy Military Installation - Bauer, Sarah (My University, 2010)
Fort McCoy biologists are concerned with emerging and invasive pathogens that could colonize fish within the waters of the military installation. An infectious disease, parasite and diet survey was conducted to document the presence of any invasive species and to establish a baseline of fish parasite communities of brook trout, brown trout, bluegill, largemouth bass, and white suckers. Fish (n = 497) were collected from 10 study sites at Fort McCoy and screened for target pathogens according to the procedures outlined in the AFS Blue Book Fish Health Section Inspection Manual. Parasite and diet data were collected on a sub-sample (n = 10-14) of each fish species from each sample site. No target viral or bacterial pathogens were detected. A total of 6,089 parasites were recovered representing 26 genera. Prevalence of infection ranged from 33% to 100% in each fish host. Two new host records were reported. Results indicated host density, water size, diet and sampling time appeared to play a role in structuring the parasite communities at Fort McCoy Military Installation
Keywords: Fishes -- Parasites -- Fort McCoy (Wis.); Fishes -- Diseases -- Fort McCoy (Wis.)